Variation in the main health-promoting compounds and antioxidant activity of different organs of Wasabi (Eutrema japonicum) from two producing areas - Di, Hongmei; Cui, Cexian; Fang, Pengcheng; Ma, Junying; He, Maolin; Li, Mengyao; Lu, Wei; Zhang, Fen; Zheng, Yangxia (Frontiers in Plant Science, 2022)
Wasabi (Eutrema japonicum), also known as Japanese horseradish, is a perennial herb widely used in Japanese cuisine for its special flavour. The health-promoting phytochemicals and antioxidant capacity of four organs (leaf, petiole, rhizome, and root) of two cultivars (Chuankui–1 and Chuankui–2) of wasabi from two producing areas, Leibo and Guangyuan in Sichuan Province, China, were investigated in this study. The results showed that leaves were rich in pigments, soluble protein, ascorbic acid, and total phenolics and had the highest antioxidant capacity. Soluble sugars were highest in the petioles and were 1.1- to 5-fold higher than those in the other three organs. Glucosinolates and glucosinolate breakdown products (GBPs) were the most abundant in rhizomes, and their maximum values were 271.61 mmol kg-1 DW and 249.78 mmol kg-1 DW, respectively. The rhizomes of Chuankui–1 in Leibo and the leaves of Chuankui–1 in Guangyuan were superior in terms of glucosinolates and GBPs. These findings provide new insights that will aid the use of wasabi cultivars; they also have implications for the environmental characteristics needed to obtain better quality wasabi products. In the future, metabolome and transcriptome can be used to analyze the potential mechanism of differences among typical varieties, origins and parts.